Retirement savings: how it fares during COVID-19 pandemic / Dahlia Ibrahim and Zuraidah Mohamed Isa - Ibrahim, Dahlia; Mohamed Isa, Zuraidah (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
Retirement savings has become a top-notch topic of recent years. The issues of concern range from unpreparedness for retirement, poor knowledge of finance and investment products, economic instability, high medical cost and constant fear that there are not enough funds to sustain lives during retirement. In Malaysia, agencies such as the Credit Counselling and Debt Management Agency (AKPK), Employee pension Fund (EPF), banks and not to leave behind, insurance companies have stepped up effort to educate the public the importance of planning for their retirement. But albeit various campaigns and programs being offered in regard to preparation for retirement, majority of the public are still slow in acting on their retirement savings. As such, there are still quite a number of retirees who are not able to support their post retirement living where it has become a trend for retirees returning to work after they have retired from their job.